2015
DOI: 10.11604/pamj.2015.21.205.5945
|View full text |Cite
|
Sign up to set email alerts
|

The clinical pattern of renal diseases in the nephrology in-patient unit of the Yaounde General Hospital in Cameroon: a five-year audit

Abstract: IntroductionKidney diseases are a growing worldwide problem and one of the major public health threats. We analyzed the spectrum of kidney diseases seen over a five-year period in the nephrology in-patient unit of the Yaounde general hospital.MethodsThis was a retrospective analysis of 225 medical records of patients admitted from January 2005 to December 2009 in the unit with a discharge diagnosis of kidney and urinary tract diseases. The first hospitalization was considered for patients admitted several time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…A Cameroonian retrospective study observed hypertension as the overall highest cause of renal conditions which is in line with our study [9]. Also, both studies recorded hypertension as the main cause of CKD; however, sepsis was the main cause of AKI in our study whiles hypertension was the main cause of AKI in their study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A Cameroonian retrospective study observed hypertension as the overall highest cause of renal conditions which is in line with our study [9]. Also, both studies recorded hypertension as the main cause of CKD; however, sepsis was the main cause of AKI in our study whiles hypertension was the main cause of AKI in their study.…”
Section: Discussionsupporting
confidence: 90%
“…e variations may be due to difference in the population setting, as well as sampling technique. At par with a study in Cameroon (61.8%), majority of our study participants (70%) had CKD; both studies employed a retrospective study design; however, the percentages vary because of the difference in our sample sizes [9]. Previous studies among renal disease patients have identified a wide range of presentations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In many instances, this nephrotoxicity is dose-dependent, and this underscores the additional importance of also understanding the mode by which people consume Traditional medicines because people with CKD may be particularly vulnerable to these effects. In the case of Aloe vera, which can cause acute tubular necrosis and acute interstitial nephritis in addition to chronic renal insufficiency, the nephrotoxicity is substantially higher with the larger doses ingested by boiling and drinking the plant [18]. Many edible plants have been associated with chronic kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…In most African countries, CKD and ESRD are very common in young adults in their economically productive years. The clinical pattern of disease is characterized by advanced CKD and acute kidney injuries secondary to preventable causes [18].…”
Section: Discussionmentioning
confidence: 99%